2016
DOI: 10.1016/j.jmig.2016.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Long-Term Bowel Symptoms After Segmental Resection of Deeply Infiltrating Endometriosis: A Matched Cohort Study

Abstract: Conclusion: Segmental bowel resection for DIE may be associated with a higher incidence of new bowel symptoms (possibly due to abdominal pain, incomplete bowel movements, and/or false alarms), but not with worse constipation or fecal incontinence, compared with surgery without bowel resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…In a series of 25 patients followed for 24 months [29], 5 of them presented with postoperative severe constipation following colorectal resection, which may be attributed to rectal neurologic sequelae, stenosis of the anastomosis, colorectal intussusception through the anastomosis, and slow-transit constipation. Another study [30], showed that surgery with segmental bowel resection for IE can be associated with new bowel symptoms such as abdominal pain, incomplete bowel movements, and/or false alarms, without worsening of constipation or fecal incontinence.…”
Section: Discussionmentioning
confidence: 99%
“…In a series of 25 patients followed for 24 months [29], 5 of them presented with postoperative severe constipation following colorectal resection, which may be attributed to rectal neurologic sequelae, stenosis of the anastomosis, colorectal intussusception through the anastomosis, and slow-transit constipation. Another study [30], showed that surgery with segmental bowel resection for IE can be associated with new bowel symptoms such as abdominal pain, incomplete bowel movements, and/or false alarms, without worsening of constipation or fecal incontinence.…”
Section: Discussionmentioning
confidence: 99%
“…noticed a trend in the relapse of symptoms 12 months after the surgery, a period at which Kössi et al 16 identified a 27% prevalence of constipation , . Another relevant study found a significant worsening of constipation symptoms in patients who underwent segmental resections compared to patients in a control group 27 .…”
Section: Discussionmentioning
confidence: 95%
“…Minor and shallower lesions are eligible to less aggressive colorectal resections, but in the case of more extensive and circumferential or multifocal involvement, these techniques may not be an option and segmental resection may be the only possible alternative 4 . Conversely, segmental resections may be responsible for the appearance of new colorectal symptoms and complications, and possibly higher postoperative morbidity 27 .…”
Section: Introductionmentioning
confidence: 99%
“…64 And although pain clearly improves after surgery for DIE, a matched cohort study with median follow-up over 10 years of 36 cases and 35 controls with DIE demonstrated that cases reported significantly more new bowel symptoms following surgery (58% in cases vs. 14% of controls, p ¼ 0.001) including abdominal pain, incomplete bowel emptying, and/or "false alarms." 68 Despite these reports, patients did not have worsening constipation or fecal incontinence than their controls who did not undergo bowel resection. Individualized counseling is recommended for DIE identified prior to surgery and involves careful discussion with the patient regarding the risks and benefits of this type of bowel surgery.…”
Section: Other Conservative Surgery Optionsmentioning
confidence: 91%